Effects of low-energy electron beam irradiation on the shelf-life and quality of vacuum-packaged beef steaks during chilled storage. (November 2022) - Yang, Jun; Wei, Wenjing; Holman, Benjamin W.B.; Shi, Hao; Zhang, Xibin; Dong, Pengcheng; Luo, Xin; Qin, Huaili; Mao, Yanwei; Zhang, Yimin
Abstract: This study evaluated the effects of different doses (0, 4, 8, 12, 16 kGy) of low-energy electron beam (LEEB; 0.2 MeV) on the quality changes of vacuum-packaged beef steaks during chilled storage for 21 days. LEEB irradiation at a low dose (4 and 8 kGy) significantly elevated the L * values of steaks, and did not deteriorate the a * values, the oxidation of lipid and protein ( P  > 0.05) compared to non-irradiated samples. LEEB irradiation (4 and 8 kGy) also significantly reduced the bacterial loads compared with non-irradiated steak, which may be due to the inactivation effect on Acinetobacter, Brochothrix thermosphacta, Carnobacterium divergens, Leuconostoc and Serratia during storage. Albeit all doses retained more acceptable sensory characteristics compared to non-irradiated samples, LEEB irradiation with >8 kGy significantly reduced the L * values and promoted protein oxidation. Overall, the LEEB irradiation with 4–8 kGy could be used as a promising innovative technology for extending the shelf-life of vacuum-packaged chilled beef steaks. Highlights: Effects of LEEB irradiation (0.2 MeV) on the quality of beef steaks were studied. LEEB irradiation reduced the bacterial loads compared to non-irradiated steaks. LEEB may inactivate Acinetobacter, B. thermosphacta, C. divergens and Leuconostoc . LEEB (4–8 kGy) elevated beef color and did not affect lipid and protein oxidation. LEEB irradiation (≤ 8 kGy) ensured the safety and quality of vacuum-packaged beef.